Zmiana masy i temperatury powierzchni szyszek sosny zwyczajnej (Pinus sylvestris L.) pod wpływem promieniowania mikrofalowego - Aniszewska, Monika (Leśne Prace Badawcze, 2016)
In this article the author investigates the change of weight and temperature of pine cones in a microwave oven over the following range of microwave radiation power (PMF): 800, 620, 440, 260 and 130 W. Cones were divided into groups according to their weight and the author examined the influence of PMF on their water content and drying rate. The process is described with the help of mathematical equations and curves. The cones were irradiated in the microwave until all cones of the given group began to open the first scales. Small cones required longer exposure times to PMF than medium and large cones in order to cause scale opening. The most efficient of the five settings was a radiation power of 620W with an exposure time to microwaves for no longer than 20 seconds. In the second part of the study, the author analyses the changes of temperature on the cone surface using a thermal imaging camera. The values of surface temperature depended on radiation power and the duration of irradiation.